Efektivitas Implementasi Ice Breaking untuk Meningkatkan Minat dan Semangat Belajar Siswa Sekolah Dasar - Mai Sri Lena; Sahrun Nisa; Tiara Utari; Hafsah Anas (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
To overcome boredom during classroom learning, teachers can conduct ice-breaking activities to keep students' learning spirit alive. This study aims to examine the implementation of ice-breaking techniques in enhancing students' interest in learning at elementary schools. The research method used in this study is descriptive with a qualitative approach. The research subjects are second-grade students and subject teachers who are the objects of the study. The research is conducted using observation and interviews with teachers and students at the elementary school that is the object of the study. The results of the study indicate that ice-breaking techniques can enhance students' interest in learning, especially in subjects considered difficult. Additionally, this technique can also strengthen the relationship between students and teachers.